2014
DOI: 10.5958/0976-4038.2014.00564.8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Non-hormonal Treatments on Postpartum True Anoestrus Crossbred Dairy Cows

Abstract: The present study was conducted to study the efficacy of different medicaments on postpartum anoestrus crossbred cows. Total of 20 post partum anoestrus crossbred cows were selected based on the case history and rectal palpation from the private dairy farm in and around the Khanapara, Guwahati, Assam. The animals were split into two groups (n=10) and treated with Vitamin A+Tonophosphan (Group 1), Vitamin A+Tonophosphan+Genital Massage (Group 2). Result of experiment revealed that number of animal responded and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
1
1
0
Order By: Relevance
“…In Estradoublesynch protocol, the mean plasma protein levels on the day of FTAI and day 12 post-AI were significantly (p<0.05) higher compared to day 0 and 9 of the protocol. Recent studies [ 13 , 33 - 34 ] also reported similar findings with different synchronization protocols in postpartum anestrus crossbred cows. Further, the overall mean protein concentrations did not differ significantly between the two protocols at day 0 and day 9.…”
Section: Resultssupporting
confidence: 57%
See 1 more Smart Citation
“…In Estradoublesynch protocol, the mean plasma protein levels on the day of FTAI and day 12 post-AI were significantly (p<0.05) higher compared to day 0 and 9 of the protocol. Recent studies [ 13 , 33 - 34 ] also reported similar findings with different synchronization protocols in postpartum anestrus crossbred cows. Further, the overall mean protein concentrations did not differ significantly between the two protocols at day 0 and day 9.…”
Section: Resultssupporting
confidence: 57%
“…Bora et al . [ 33 ] observed higher plasma cholesterol concentrations on the day of induced estrus and on day 20 than day 10 or 0 of treated respondent postpartum anestrus crossbred cows. However, in earlier studies employing Ovsynch, Cosynch, PRID, etc., the plasma cholesterol levels were not influenced significantly between sampling days in anestrus cattle [ 4 , 32 , 34 ].…”
Section: Resultsmentioning
confidence: 99%